Growth Inhibition of Cocoa Pod Rot Fungus Phytophthora palmivora byPseudomonas fluorescence and Bacillus subtilis bacteria - Sakti Widyanta Pratama; Sri Sukamto; Lis Nur Asyiah; Yeni Vida Ervina (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
Black pod disease caused by Phytophthora palmivorafungus is one of the important diseases on cocoa crop. Pod rot is the most important disease because it may cause loss of cocoa pod. Until now, the fungal pathogen of cocoa black pod disease is still a crucial problem and there is no fungicide that is really effective against the disease. One alternative to control the cocoa black pod disease is by using biological agents as biofungicide, including utilizing Pseudomonas fluorescenceand Bacillus subtilis bacteria. The research was done by isolation of P. palmivora from infected pods of Kaliwining Experimental Station to obtain pure cultures of fungus and by multiplication of P. fluorescence and B. subtilis. Antagonist test was performed by inoculating P. palmivora into a petri dish in a distance of 3 cm from the edge. P. fluorescenceand B. Subtilis were inoculated into petridishes in three days after the fungal treatment. Control was inoculated with isolate of P. palmivora only. Fungal growth was measured everyday by measuring radius of fungal colonies first time 24 hours after inoculation. Growth of Phytophthora palmivora in the two treatmens were used to calculate the percentage of inhibition. The results of this study indicated that P. fluorescence and B. subtiliswere able to inhibit fungal growth of P. palmivora. Both bacterial antagonists had the same effectiveness in inhibiting the growth of P. palmivora fungus based on the percentage of inhibition and effectiveness criteria. Based on the results of translucent zones indicated that B. subtiliswas more powerfull in inhibiting growth of P. Palmivora compared to P. fluorescence. Key words: Black pod disease of cocoa, biological control, Phytophthora palmivora, Pseudomonas fluorescence, Bacillus subtilis